Implementation of a novel continuous solid/liquid mixing accessory for 3D printing of dysphagia-oriented thickened fluids. (November 2021) - Diañez, I.; Gallegos, C.; Brito-de la Fuente, E.; Martínez, I.; Valencia, C.; Sánchez, M.C.; Franco, J.M.
Abstract: This paper describes the implementation and evaluation of an accessory designed and manufactured to be adapted to a 3D printer to allow the in situ and continuous mixing of powder and liquid feeds. In particular, the capacity of this accessory to correctly mix a dysphagia-oriented commercial powder thickener with several conventional fluids (i.e. water, juice, and milk) was studied. Target thickener concentrations were defined in order to achieve mixtures with viscosities corresponding to the textures established by the National Dysphagia Diet Task Force (NDD)—nectar-like, honey-like, and spoon-thick—for thickened fluids. Both the accuracy of the solid content and the rheological response of the obtained mixtures were evaluated. Although fluctuations were observed in the concentrations of the mixtures obtained by continuous mixing with respect to the target values, the viscosities obtained were within the limits established for each of the desired textures. The thickened fluids processed using the 3D printing mixing accessory showed viscosities very similar to their hand-mixed counterparts and a higher degree of structuration, especially when printed at low mass flow rates, as well as a lower amount of entrapped air. This method of preparation allows the production of thickened fluids with more appealing shapes and colours for the long-term dysphagia management, improving the quality of life of patients with dysphagia, and promoting treatment compliance. Graphical abstract: Image 1 Highlights: Development of a solid/liquid mixing device (MIX3D) for 3D printers. MIX3D was applied to the preparation of dysphagia-oriented thickened fluids. Thickener content was set to obtain nectar-like, honey-like and spoon-thick textures. Rheological properties of mixtures are comparable to those of hand-prepared fluids. Water, orange juice and skimmed milk have been successfully thickened with MIX3D.